Psychotic-like experiences and happiness in the English general population - Koyanagi, Ai (Journal of affective disorders, 2017)
Psychotic-like experiences (PLEs) have been associated with a variety of adverse outcomes but how they affect happiness in individuals with PLE is unknown. Thus, the aim of the study was to assess the association between PLEs and happiness, and the factors that may influence this association. Nationally representative data from the 2007 Adult Psychiatric Morbidity Survey including adults aged ≥ 16 years was analyzed. The Psychosis Screening Questionnaire was used to assess past 12-month PLE. Individuals who endorsed at least one of the following were considered to have any PLE: thought control, paranoia, strange experiences, auditory hallucinations. Happiness (3-point scale) was assessed with a validated question with higher scores indicating lower levels of happiness. The association between PLE and happiness was assessed by multivariable ordinal logistic regression. Mediation analysis was also performed. Among the 7363 individuals included in the analysis, the prevalence of any PLE increased with decreasing levels of happiness [very happy (2.3%), fairly happy (5.4%), not too happy (14.9%)]. This was also shown in the multivariable analysis adjusted for sociodemographic factors and stressful life events (from very happy to not too happy: OR = 2.41; 95%CI = 1.86–3.12). Mediation analysis showed that anxiety disorders explained the largest proportion of the association (38.8%) followed by depressive episode (28.5%), insomnia (21.9%), disability (16.5%), pain (12.5%), social support (10.0%), and physical health conditions (6.0%). The cross-sectional design limits causal inference. Interventions to identify and address conditions that may have a negative impact on happiness in individuals with PLE may be important to improve their well-being. •Individuals with psychotic-like experiences (PLEs) were more likely to be unhappy.•Co-existing mental disorders largely explained this association.•Factors which may help improve well-being in people with PLEs were identified.